Bachelard et les philosophies de l’Orient (Altre Modernità, 2012)
Although deeply rooted in its time, Bachelard's work dedicated to the Poetic allows many links with the religions of the Far East. Imaginary’s partition into a feminine side and a masculine side, first of all, is a reminiscence of the Yin and Yang of Taoism. But other concepts, such as the “sentiment cosmique” (cosmic feeling) – the sense of being one with the cosmos activated at the end of certain dreams, stimulated by the contact with certain elements – allow a parallel with the Buddhist’s Nirvana and the unity sought in the Tao. Is it necessary to interpret these similarities in terms of inspiration that Bachelard would have drawn from the most famous authors of oriental literature, since he was a reader as eclectic as bulimic, or should we see in this interpretation of the world, at least partially similar with the one of the great sages of the East, a very personal rediscover, inherent to his method, the phenomenology?